Prevalence of Tourette syndrome among children and adolescents in the United States, 2016-2022 - Yuhong Xiong; Matthew O'Brien; Wenhan Yang; Xiaodong Zang; Wei Bao; Guifeng Xu (BMC, 2024)
Abstract Background Tourette syndrome (TS) is a neurodevelopmental disorder. The prevalence of TS in 2016-2017 has been reported; however, little is known about the current prevalence and trend in children and adolescents with TS. This study aimed to estimate the prevalence and trend of Tourette syndrome (TS) among US children and adolescents aged 0-17 years from 2016 to 2022. Methods We analyzed data from a nationally representative sample of 278,472 children and adolescents aged 0-17 years who participated in the 2016-2022 National Survey of Children's Health (NSCH), a nationwide, population-based, cross-sectional survey of US children and adolescents. TS was defined as the affirmative response in the questionnaire completed by a parent or guardian. Results Among the 278,472 children and adolescents enrolled, 754 had been diagnosed with TS, with an overall prevalence of 0.23% in all children and adolescents aged 0-17 years. The weighted prevalence by age group was lower than 0.01% in children aged 0-2 years, 0.05% in children aged 3-5 years, 0.28% in children aged 6-11 years, and 0.38% in adolescents aged 12-17 years. There were significant sex and racial/ethnic differences in the overall prevalence of diagnosed TS (i.e., 0.35% in boys and 0.11% in girls, 0.22% in Hispanics, 0.28% in non-Hispanic whites and 0.16% in non-Hispanic blacks). There was no significant change in the estimated prevalence of TS from 2016 to 2022. Conclusion Based on nationally representative data, this study found that the national prevalence of TS among the US children and adolescents differed by sex and race/ethnicity but remained stable from 2016 to 2022.